The practice of Unit Penyelenggaraan in maintaining air conditioning system in UiTM Shah Alam: a critical analysis / Anwar Abdul Rahman and Maz Izha Samsudin - Abdul Rahman, Anwar; Samsudin, Maz Izha (2000)
The objective of this project is to improve the maintenance management system of Unit Mekanikal (Penyaman Udara), Pejabat Penyelenggaraan, Universiti Teknologi MARA, Shah Alam, Selangor. We started the project by examining their work condition, work culture and data management. Next, we identified the problems and analysed them to provide the best possible solutions. Some of these problems were found by comparing the operation of Unit Penyaman Udara with other organisations while others were found through observation during our practical training at the Unit. The proposed solutions were based on theory for technical problems as well as from human or non-human based condition analysis. Most of them were gathered by conducting interviews with the staff of Unit Penyaman Udara and some other organisations, from the technical support level to the executive and/or engineer level. We also found other option that is by implementing the Total Preventive Maintenance (TPM) or Total Quality Management (TQM) in their maintenance management system. With some aids that needed in both tools, it will help Unit Penyaman Udara to elevate the productivity of staffs work quality. In experiencing the computer science and information technology advancement, Unit Penyaman Udara should able to use the Computerised Maintenance Management System (CMMS) in their system for having more competitive staff in doing better management and maintenance work.